THE EFFECTI-VENESS OF THE POLICE FUNCTION IN TACKLING THE OCCURRENCE OF PERSECUTION - Andi Azis Kaliabo; Hambali Thalib; Said Sampara (P3M Stia Al Gazali Barru and Meraja media, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal